The Emerging Role of RNA N6-Methyladenosine Modification in Pancreatic Cancer - Hu, Xiaoge; Lei, Xiangxiang; Guo, Jinhui; Fu, Wen; Sun, Wen; Lu, Qiliang; Su, Wei; Xu, Qiuran; Tu, Kangsheng (Frontiers in Oncology, 2022)
Pancreatic cancer (PC) is one of the most common malignant cancers, ranking the seventh highest causes of cancer-related deaths globally. Recently, RNA N6-methyladenosine (m6A) is emerging as one of the most abundant RNA modifications in eukaryotes cells, involved in multiple RNAs processes including RNA translocation, alternative splicing, maturation, stability, and degradation. As reported, m6A was dynamically and reversibly regulated by its “writers”, “erasers” and “readers”. Emerging Increasing evidences hasve revealed the vital role of m6A modification in the development of multiple types of cancers including PC. Currently, aberrant m6A modification level has been found in both PC tissues and cell lines. Moreover, abnormal expression of m6A regulators and m6A-modified genes have been reported to contribute to the malignant development of PC. Here in this review, we will focus on the function and molecular mechanism of m6A-modulated RNAs including coding RNAs as well as non-coding RNAs. And then summarize the m6A regulators and reveal will be summarized to reveal their potential applications in the clinical diagnosis, prognosis and therapeutics of PC.